Description of Basiria birjandiensis n. sp (Nematoda: Tylenchidae) from South Khorasan province with a checklist of the family Tylenchidae Örley 1880 from Iran - Alvani, Somaye; Mahdikhani-Moghadam, Esmat; Rouhani, Hamid; Mohammadi, Abbas; Karssen, Gerrit (Zootaxa, 2016)
In order to identify plant–parasitic nematodes (family Tylenchidae Örley 1880) associated with Ziziphus zizyphus in Iran, 360 soil and root samples were collected from South Khorasan province during 2012–2014. Herein, a new species of Basiria and several known members of the family Tylenchidae are reported. B. birjandiensis n. sp. is characterized by short body length (584–748 µm [660.6±72.3]), lip region with flat apex, stylet 11–12 µm (11.3±0.5), excretory pore position varying from isthmus level to the middle of the basal bulb (78–91 µm from the anterior end of the body), post–vulval uterine sac 8–14 µm (10.7±1.9) long, filiform tail (151–181 µm, c= 3.7–4.2, c´= 14.3–17.2) and body annuli 0.5–1 µm (0.6±0.1) wide. A checklist of Tylenchidae species from Iran is also presented.